PerbedaanPengaruh Nefroprotektor Ekstrak Kunyit, Ekstrak Temulawak, dan Kombinasinya Terhadap Kerusakan Histologis Sel Ginjal Mencit yang Diinduksi Parasetamol - Aulia Agung Sanubari; . Muthmainah; . Isdaryanto (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Turmeric and xanthorrhiza have been known to contain curcumin, and specially xanthorrhiza also contain xanthorrhizol that may exhibit significant protection of kidney cells from free radicals. This study has carried out to evaluate difference nefroprotector effect between turmeric, xanthorrhiza, and combination turmeric and xanthorrhiza on histological damage of kidney cells that induced paracetamol in mice. Methods: Present study was experimental laboratory research with post test only controlled group design.Samples were 30 male Swiss webster mice (2-3 months old) weighing+20 g, and they were divided equally into 5 groups, 6 mice each group. Sampling technique in this research was incidental sampling.KK (-) and KK (+) were given aquadest for 14 days. KP1 was given turmeric extract with the dose of 2,8 mg/20 g body weight of mice, KP2 was given xanthorrhiza extract with the dose of 14 mg/20 g body weight of mice, and KP3 was given combination of turmeric extract with dose 2,8 mg/20 g body weight of mice and xanthorrhiza extract with dose 14 mg/20 g body weight of mice for 14 days.Paracetamol was given to groups ofKK (+), KP1, KP2, and KP3on the 12th, 13th, and 14th day. On day-15th, micewere sacrificedandkidneys weretakento makepreparationsby paraffinblockmethodandHEstaining. Kidney histological features were assessed based on quantifying ofpyknosis, karyorrhexis, and karyolysis. Data were analyzed with the Kruskall-Wallis test (?=0.05) and continued with Mann-Whitney test (?=0.05). Results: Mean KK(-) : 10,331,40, KK(+) : 25,883,19, KP1 : 152,37, KP2 : 11,582,33, and KP3 : 131,92. Result of statistically data analysis showed that there was a significant difference of kidney damage score between all pairs of groups, except KK(-) - KP2 was not significant. Conclusion: There was a difference nefroprotector effect between turmeric, xanthorrhiza, and combination of them on histological damage of kidney cells that induced paracetamol, and xanthorrhiza extract at dose 14 mg/20 g body weight of mice had a better effect than turmeric extract or combination of them. Keywords: turmeric extract, xanthorrhiza extract, nefroprotector, kidney cells damage.